"Back off, man, I'm a scientist!" When marine conservation science meets policy. (October 2015) - Rose, Naomi A.; Parsons, E.C.M.
Abstract: There is often a basic tension at the boundary between science and policy – the former seeks unbiased, objective descriptions of reality, while the latter must incorporate various factors in its development, including values, ideologies, economics, biases, and emotions. Problems may arise if, and when, marine scientists who enter the policy arena fail to understand these differing priorities, and we describe some common pitfalls. Various strategies are presented for marine conservation scientists to consider in order to avoid or minimize misunderstandings, especially with the media. Conflict of interest issues and public perception of bias are also addressed, as is misuse of research results and whether scientists have an obligation to correct misrepresentation of their research. Finally, we consider how marine scientists should address the inherent uncertainty in their results when those results are used to develop policy, including the importance of incorporating the Precautionary Principle when making science-based policy. Highlights: There a high degree of science illiteracy among policy-makers (particularly in the US) and scientists urgently need to engage in the policy process. Few scientists are truly independent and perceptions of conflicts of interest are inevitable when engaging in the policy process and these are to be accepted and mitigated and not ignored. Scientists engaging in policy should be precautionary; be wary of statements being taken out of context; not get defensive when disagreement occurs; and be wary that caveats will be ignored and arguments oversimplified. Scientists should actively correct misrepresentations of science and develop their communication skills to ensure clear, concise advice. To encourage scientist engagement in the policy process, evaluation of faculty and researchers should give credit for work that has "real world" policy/regulatory impact.